Edukasi Filosofi Kearifan Lokal Bagi Gen Z Suku Buton - Poniasih Lelawatty; Suryo Ediyono (LPPM UNIVERSITAS DIAN NUSWANTORO, 2026)
This community service activity aims to improve Generation Z’s understanding of the local wisdom of the Butonese community amid the challenges of globalization and digitalization that may weaken cultural identity. The selection of this topic is based on the low initial level of participants’ understanding, as reflected in pre-test results dominated by the “not understood” category. The method used is a qualitative descriptive approach through educational activities, interactive discussions, and material presentation based on seven elements of local wisdom, analyzed using ontological, epistemological, and axiological perspectives. The results indicate a significant improvement in participants’ understanding, marked by an increase in the “understood” category from 12.00% to 69.33% and a substantial decrease in the “not understood” category. These findings demonstrate that local wisdom-based education is effective in enhancing cultural literacy and awareness among young generations. Therefore, this activity successfully strengthens the relevance of local wisdom as a contextual knowledge source in modern life.